ANTIBIOTIC USE IN PREVENTION OF ANAL FISTULAS FOLLOWING INCISION AND DRAINAGE OF ANORECTAL ABSCESS: A SYSTEMATIC REVIEW - Almalik Saputra, Yusuf (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Perianal abscess is a condition that arises with an extraordinarily high frequency in general surgery. Despite the fact that the majority of patients reported here suffered from a relatively simple and uncomplicated disease, as estimated retrospectively, the data presented suggest that there is an alarmingly high rate of acquired drug resistance in bacteria detected in purulence swabs from perianal abscesses obtained during surgical drainage procedures in approximately 27% of all patients, especially in patients with a more severe disease. This rate is especially high in perianal abscess patients. The primary objective of surgical treatment for anal fistulain-ano is to obliterate the internal fistulous opening and any associated epithelialized tracks while retaining the anal sphincter's function. Due to the fact that no single surgery is appropriate for the treatment of all fistulas, treatment must be directed by the fistula's etiology and architecture, the degree of symptoms, the patient's comorbidities, and the surgeon's experience. One must consider the trade-off between sphincter division extent, surgical healing rates, and functional compromise. Following incision and drainage of anorectal abscesses, antibiotic therapy is related with a decreased likelihood of fistula formation. An empiric 5-10-day course of antibiotics following surgical drainage may prevent fistula formation in otherwise healthy patients, notwithstanding the low quality of the data.